Creative city narratives vs. lived realities: an ethnographic study of UNESCO designation in Como, Italy - Raffa, Massimiliano (Frontiers in Communication, 2025)
IntroductionThis study examines how cultural producers perceive and interpret the UNESCO Creative City designation, focusing on Como, Italy, following its 2021 inclusion in the network. Anchored in critical urban theory and cultural sociology, the research investigates how institutional narratives of creativity intersect with the interpretive frameworks through which cultural actors understand their work.MethodsThe research employed ethnographic methods, including semi-structured interviews with diverse cultural producers (theatrical practitioners, visual artists, craftspeople, musicians, filmmakers, venue operators), participant observation at cultural events, and document analysis. Data were analyzed using constructivist grounded theory principles.ResultsFindings reveal three interrelated disjunctures: (1) institutional disconnection, expressed through parallel cultural worlds governed by conflicting evaluative logics; (2) spatial constraints, exacerbated by tourism intensification, that undermine conditions for creative practice; and (3) network fragmentation, which cultural producers seek to overcome through emergent forms of solidarity. The study demonstrate these tensions exist alongside the potential for virtuous relationships between Creative City designations and cultural tourism development, while also reflecting how local cultural forms are transformed into symbolic capital within broader urban development projects.DiscussionThe study highlights significant tensions between top-down policy frameworks and bottom-up cultural labor, showing how local creative communities actively reinterpret, resist, and reshape institutional discourses. By centering cultural producers’ meaning-making practices, the research contributes to debates on culture’s instrumentalization in urban governance and offers insights for more inclusive, sustainable, and dialogic cultural policy approaches.